EphA2 as a Diagnostic Imaging Target in Glioblastoma: A Positron Emission Tomography/Magnetic Resonance Imaging Study. Issue 6 (1st July 2015) - Puttick, Simon; Stringer, Brett W.; Day, Bryan W.; Bruce, Zara C.; Ensbey, Kathleen S.; Mardon, Karine; Cowin, Gary J.; Thurecht, Kristofer J.; Whittaker, Andrew K.; Fay, Michael; Boyd, Andrew W.; Rose, Stephen
Noninvasive imaging is a critical technology for diagnosis, classification, and subsequent treatment planning for patients with glioblastoma. It has been shown that the EphA2 receptor tyrosine kinase (RTK) is overexpressed in a number of tumors, including glioblastoma. Expression levels of Eph RTKs have been linked to tumor progression, metastatic spread, and poor patient prognosis. As EphA2 is expressed at low levels in normal neural tissues, this protein represents an attractive imaging target for delineation of tumor infiltration, providing an improved platform for image-guided therapy. In this study, EphA2-4B3, a monoclonal antibody specific to human EphA2, was labeled with 64 Cu through conjugation to the chelator 1, 4, 7-triazacyclononane-1, 4, 7-triacetic acid (NOTA). The resulting complex was used as a positron emission tomography (PET) tracer for the acquisition of high-resolution longitudinal PET/magnetic resonance images. EphA2-4B3-NOTA- 64 Cu images were qualitatively and quantitatively compared to the current clinical standards of [ 18 F]FDOPA and gadolinium (Gd) contrast–enhanced MRI. We show that EphA2-4B3-NOTA- 64 Cu effectively delineates tumor boundaries in three different mouse models of glioblastoma. Tumor to brain contrast is significantly higher in EphA2-4B3-NOTA- 64 Cu images than in [ 18 F]FDOPA images and Gd contrast–enhanced MRI. Furthermore, we show that nonspecific uptake in the liver and spleen can be effectively blocked by a dose of nonspecific (isotype control) IgG.